The impact of informativeness, credibility, entertainment, and irritation on Gen Z’s purchase intention mediated by advertising value in the case of Instagram Stories Advertising - Jaya Saputra; Jeovanni Jonson (iBuss Management, 2020)
As the number of Gen Z increases, many people believe that this generation will bring a huge impact to global expenditure and also the world’s economic landscape in the future. One of the distinguish behaviour of Gen Z is their spending time on social media that surpasses other generations. Gen Z consider social media as important aspect in their daily life, even in influencing their purchase decision. Moreover, the most used social media of Gen Z is Instagram. Therefore, the researchers are eager to understand the methods of having a good advertisement in Instagram Stories to engage Gen Z. This research will use the modified advertising value theory from Ducoffe (1995); the relationship between informativeness, credibility, entertainment, and irritation towards purchase intention with advertising value as the mediator in the case of Instagram Stories Advertising. This research focuses on the Generation Z Instagram users in Indonesia and will be done by a quantitative approach. Simple random sampling will be used as the sampling design with online questionnaires as the method to obtain the data. Moreover,133 respondents have answered the questionnaire and analysed further with path analysis using multiple linear regression and Sobel Test. As the result, it was found that informativeness is fully mediated and entertainment is partially mediated by advertising value in influencing purchase intention. However, this research result found that credibility and irritation is insignificant in influencing purchase intention and advertising value. Keywords: Advertising Value, Purchase Intention, Advertising Attributes, Instagram, Instagram Stories Advertising